The Objectivity of Accountants' Litigation Support Judgments - Ponemon, Lawrence A. (The Accounting Review, 1995)
[This study examines accountants' objectivity when serving as a litigation specialist and expert witness on legal cases. Its purpose is to determine whether professional objectivity, in generating a fair and unbiased accounting estimate, will be influenced by the possible conflicts of interest inherent in the litigation support role. Employing litigation specialists and auditors from two firms, and the Defining Issues Test as a psychometric for practitioners' ethical reasoning, this research examines client advocacy on a damage valuation experiment manipulating the client's legal position. Results show that domain-specific experience coupled with ethical reasoning reduces the extent of bias or "side taking" in litigation support judgment.]